2009
DOI: 10.1177/1043454209340319
|View full text |Cite
|
Sign up to set email alerts
|

Growth Velocity in Pediatric Bone Marrow Transplantation: Significance of Donor Type and Treatment Factors

Abstract: Children who have undergone bone marrow transplantation (BMT) often have decreased growth. Growth is a multifactorial process, and the factors that influence growth after BMT are not completely understood. The authors hypothesized that donor type may be a factor influencing growth. Sixty-five children and adolescents who underwent BMT (32 related matched, 33 unrelated matched) were evaluated. Growth velocity (height standard deviation) was assessed prior to and 2 years following BMT. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…HSCT usually has an impact on all these factors and, thus, patients are at risk for alterations in growth. 24 In a prospective study among 49 pediatric HSCT patients, the most profound loss of bone mineral density (BMD) was within the first 6 months following HSCT, similar to what has been reported in adults. In this study, some children showed recovery; however, 33% remained osteopenic and 19% osteoporotic at 1 year following HSCT.…”
Section: Side Effectsmentioning
confidence: 65%
“…HSCT usually has an impact on all these factors and, thus, patients are at risk for alterations in growth. 24 In a prospective study among 49 pediatric HSCT patients, the most profound loss of bone mineral density (BMD) was within the first 6 months following HSCT, similar to what has been reported in adults. In this study, some children showed recovery; however, 33% remained osteopenic and 19% osteoporotic at 1 year following HSCT.…”
Section: Side Effectsmentioning
confidence: 65%